Using Rapid Design Thinking to Overcome COVID-19 Challenges in Medical Education. (January 2021) - Thakur, Anupam; Soklaridis, Sophie; Crawford, Allison; Mulsant, Benoit; Sockalingam, Sanjeev
Abstract : The rapid rise of cases of coronavirus disease 2019 (COVID-19) has led to the implementation of public health measures on an unprecedented scale. These measures have significantly affected the training environment and the mental health of health care providers and learners. Design thinking offers creative and innovative solutions to emergent complex problems, including those related to training and patient care that have arisen as a result of the COVID-19 pandemic. Design thinking can accelerate the development and implementation of solution prototypes through a process of inspiration, ideation, and implementation. Digital technology can be leveraged as part of this process to provide care and education in new or enhanced ways. Online knowledge hubs, videoconference-based interactive sessions, virtual simulations, and technology-enhanced coaching for health care providers are potential solutions to address identified issues. Limitations of this model include inherent bias toward utilitarian instead of egalitarian principles and the subsequent threat to diversity, equity, and inclusion in solutions. Although medical educators have embraced digital transformation during the COVID-19 pandemic, there is a need to ensure that these changes are sustained.